1995
DOI: 10.1557/proc-417-271
|View full text |Cite
|
Sign up to set email alerts
|

AlInAs Band Gap Modulations Observed by Tem and Optical Measurements

Abstract: At a low MBE growth temperature (400°C), an anisotropic composition modulation has been observed by Transmission Electron Microscopy (TEM) on AIlnAs layers. Optical measurements have been performed on these samples and compared with classical AllnAs grown at 530°C. We show the clustering “organization” on the low temperature layers and we propose some hypothesis to explain the composition modulation effects on the AlInAs optical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The InAIAs buffer layer is not necessarily homogeneous since several forms of compositional modulation have been observed in MBE In.AIAs epitaxial layers [19][20][21]. In our InAlAs buffer layers a very weak lateral composition modulation was observed, in plan-view TEM studies, along [110] with a wavelength of =9 nm similar to that reported previously [20,21] in lMBE InAlAs layers grown at lower temperatures. The elastic stresses associated with this compositional modulation could influence the nucleation of the first InAs layer of the SPS [18].…”
Section: Isupporting
confidence: 82%
“…The InAIAs buffer layer is not necessarily homogeneous since several forms of compositional modulation have been observed in MBE In.AIAs epitaxial layers [19][20][21]. In our InAlAs buffer layers a very weak lateral composition modulation was observed, in plan-view TEM studies, along [110] with a wavelength of =9 nm similar to that reported previously [20,21] in lMBE InAlAs layers grown at lower temperatures. The elastic stresses associated with this compositional modulation could influence the nucleation of the first InAs layer of the SPS [18].…”
Section: Isupporting
confidence: 82%
“…Results are published elsewhere [8]. The half widths at half maximum of PL peaks are rather large when compared with the theoretical limits for alloy scattering in this system and with the best experimental result which is about 2.8meV at 4K [9].…”
Section: Bulk Layersmentioning
confidence: 66%
“…The AlInAs PR feature is very large, indicating the modulation composition of this alloy. 13 The PR transitions corresponding to the quantum confined levels in the quantum well are fitted using the first derivative functional form ͑FDFF͒ of the dielectric function, which is appropriate in the case of confined systems 14…”
Section: Photoreflectance Spectra Of the Inalas/ingaas Quantum Wellmentioning
confidence: 99%